2022
DOI: 10.7759/cureus.26268
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Ophthalmic Plastic and Reconstructive Surgery Fellowship Program Directors in the United States

Abstract: This study aims to examine the demographic features, academic backgrounds, and scholarly achievements of ophthalmic plastic and reconstructive surgery (OPRS) fellowship program directors (PDs) in the United States. MethodsIn this cross-sectional analysis, publicly accessible sources were accessed in March 2022 to collate the demographic and academic profiles of PDs of American Society of Ophthalmic Plastic and Reconstructive Surgery (ASOPRS)-accredited OPRS fellowships. Differences by gender and program rank w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…The number of publications reflects the publication contributions of a country, institution, or individual but not the impact of those contributions. To overcome this drawback, the average citations per article [ 66 , 67 ] and H-index [ 68 , 69 , 70 , 71 , 72 ] were introduced to the quality evaluation. In this study, countries were ranked based on the contribution percentage, and we found that the top five countries with outstanding contributions to TB vaccine research were the USA, the UK, France, Germany, and Denmark ( Figure S1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The number of publications reflects the publication contributions of a country, institution, or individual but not the impact of those contributions. To overcome this drawback, the average citations per article [ 66 , 67 ] and H-index [ 68 , 69 , 70 , 71 , 72 ] were introduced to the quality evaluation. In this study, countries were ranked based on the contribution percentage, and we found that the top five countries with outstanding contributions to TB vaccine research were the USA, the UK, France, Germany, and Denmark ( Figure S1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 50 years, women have gone from comprising one-fifth of the medical workforce to representing more than half of newly admitted medical students in 2020. 31 Similar to other medical and surgical specialties, OB-GYN was historically a predominantly male field. In recent decades, we have observed an increase in the number of female-identifying trainees.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study are consistent with trends in medicine. Over the past 50 years, women have gone from comprising one-fifth of the medical workforce to representing more than half of newly admitted medical students in 2020 31 . Similar to other medical and surgical specialties, OB-GYN was historically a predominantly male field.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations